Digital Literacy, Pedagogical Insight, and Self-Belief: An Exploration of Pre-Service Teacher Z-Generation - Fitra Jaya (Universitas Muhammadiyah Mataram, 2024)
Generation Z currently dominates the student population in pre-service teacher education programs. Analyzing the differences in characteristics between Generation Z pre-service teachers and those from previous generations is crucial. In the ever-evolving digital era, Generation Z pre-service teachers need to possess strong digital literacy, deep pedagogical understanding, and adequate self-confidence to meet the demands of the digital age. This study aims to investigate the role of digital literacy and self-efficacy among pre-service teachers as mediators in their relationship with technological pedagogical content knowledge (TPACK). This research is quantitative in nature. Data were collected from 105 Generation Z pre-service teachers from various study programs across two different provinces in Indonesia. The instruments used to measure the variables included questionnaires on digital literacy, self-efficacy, and TPACK. The Structural Equation Model (SEM) was employed to analyze the structural relationships. The findings reveal that Generation Z pre-service teachers have a strong inclination towards digital literacy, which influences their pedagogical insights in implementing technology in teaching and learning processes. The development of pre-service teacher training programs is necessary to adapt to the needs of Generation Z and the rapid technological advancements in the future. A solid grasp of digital literacy and pedagogical insights can effectively prepare qualified educators